2022
DOI: 10.1097/cad.0000000000001304
|View full text |Cite
|
Sign up to set email alerts
|

TRIM72 exerts antitumor effects in breast cancer and modulates lactate production and MCT4 promoter activity by interacting with PPP3CA

Abstract: A hypoxic tumor microenvironment (TME) promotes cancer progression, yet its value as a therapeutic target remains underexploited. Tripartite motif-containing 72 (TRIM72) may protect cells against various stresses including hypoxia. Recently, low TRIM72 expression has been implicated in cancer progression. However, the biological role and molecular mechanism of TRIM72 in breast cancer (BC) remain unclear. Herein, we analyzed the TRIM72 expression in BC tissue and cell lines by western blot (WB) and quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… 21 Overexpression of TRIM72 is reported to inhibit tumor proliferation and invasion in vitro and in a xenograft tumor model in breast cancer progression. 22 The “DEL” mutation in the “chr3:57896344-57896845” significantly increased the activity of the enhancer (log2FC = 2.31) in LumB subtype, which in turn was associated with the downregulation of potential target genes, such as lncRNA FLNB-AS1, FLNB, and SLMAP. The lncRNA FLNB-AS1 was significantly downregulated (log2FC = −2.34) in breast cancer samples with the mutation-driven enhancer, and literature has confirmed that FLNB-AS1 is positively correlated with the survival probability of patients with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“… 21 Overexpression of TRIM72 is reported to inhibit tumor proliferation and invasion in vitro and in a xenograft tumor model in breast cancer progression. 22 The “DEL” mutation in the “chr3:57896344-57896845” significantly increased the activity of the enhancer (log2FC = 2.31) in LumB subtype, which in turn was associated with the downregulation of potential target genes, such as lncRNA FLNB-AS1, FLNB, and SLMAP. The lncRNA FLNB-AS1 was significantly downregulated (log2FC = −2.34) in breast cancer samples with the mutation-driven enhancer, and literature has confirmed that FLNB-AS1 is positively correlated with the survival probability of patients with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of ULK1 complex is essential for phagophore and regulated by PI3K-AKT-mTOR pathway [ 39 ]. Recent studies have shown that TRIM72 could suppress the PI3K-AKT-mTOR pathway induced by hypoxia [ 58 ]. Here, we also found that AAV-TRIM72 decreased the p-PI3K and p-AKT expression (Figures 6(a) – 6(c) ).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of ubiquitinrelated genes in the cancer genome atlas queue revealed an association between MG53 and the prognosis of renal clear cell carcinoma (Wu et al, 2021). MG53 can also impede breast cancer progression by suppressing the activation of the PI3K/Akt/mTOR pathway (Wang et al, 2022). Further investigation is warranted to explore the potential anti-tumor effects of MG53 in various malignancies.…”
Section: Mg53 and Other Cancersmentioning
confidence: 99%